EFFICIENCY INDICATORS OF CONSTRUCTION ENTERPRISES AND CHARACTERISTICS OF INNOVATIONS IMPLEMENTED IN THEM - Mamajonova Nodirakhon Alisher kizi (The Conference Hub, 2025)
This article discusses the main directions of the use of innovation in the country, the practical activity of the industrial enterprises and the efficiency of performance indicators.
Keywords: enterprise, effectiveness, innovation, efficiency indicators, fundamental researches, profitability.